Behaviour of reinforced stone columns subjected to static shear loading conditions - S. V. Rashma, R.; Shivashankar, R.; R. Jayalekshmi, B. (International Journal of Engineering and Technology, 2019)
Stone columns, also known as granular piles, are an effective way of improving weak grounds which are having low bearing capacities, high compressibilities and low resistances to earthquakes. Stone column treatment is preferred to support low rise buildings or embank-ments on weak soils, which can tolerate some settlements. Stone columns mitigate liquefaction by providing shortest path for excess pore water to escape through the voids in stone columns. Another advantage of using stone column is that it can speed up consolidation process and the construction works can be started without much delay and thereby managing time and cost of construction.The failure mechanism of stone column include bulging failure (long columns) or shear or punching failure. The failure mode depends on many parameters like strength, stiffness, length, diameter of column, reinforcement used, location, spacing, end condition, soft soil etc. Stone columns may fail by shear when it is subjected to horizontal load or movement. Columns mostly take vertical loads. When column supported embankments are huge, columns will undergo shear failure. It has been reported that the short end bearing and floating stone columns can fail in shear. Horizontal shear is also reported as one of the possible column failure mode under embankment.In an embankment supported by stone columns, the columns in the middle is mostly subjected to vertical loading. But, the columns near to the toe of the embankment is subjected to lateral loading. The lateral load is predominantly acting on columns which are placed near to the toe of the embankment. The present study is focused on understanding the behaviour of porous concrete column improved ground subjected to static shear loading. Present study is aiming to study the behaviour of plain and reinforced stone columns under static shear loading conditions, with the help of numerical modelling using available software ABAQUS. The results of the study indicate that the porous concrete column improved soft/weak ground is able to take significantly more shear loads under less settlements under static lateral loading conditions and that porous concrete columns can withstand significant shear stresses.Â